Asssesing the effectiveness and impact of agricultural water management interventions: the case of small reservoirs in northern Ghana - Acheampong, D.; Balana, Bedru; Nimoh, F.; Abaidoo, Robert C. (Elsevier, 2018)
Agricultural water management, particularly management of multi-purpose small reservoirs (SRs) in drier savanna areas of the northern Ghana, is being promoted as a key solution to improve agricultural production, enhance food security and livelihoods of smallholder farm households. However, little empirical evidence exist on how effective these small water infrastructures are in terms of delivering multiple benefits and their impact on the livelihood of smallholder farmers. This study assessed the effectiveness and impact of the small reservoirs on smallholder vegetable farmers in northern Ghana. A participatory rating method using a 5-point Likert-scale was used to assess the effectiveness of SRs in delivering multiple livelihood benefits and an endogenous switching regression model was applied to assess the SRs’ impact using a primary data collected from 328 randomly sampled vegetable farmers. Results from the Likert scale analysis show that most of the SRs are either dysfunctional or underutilized and not effective in delivering multiple benefits. Results from the endogenous switching regression model show that there is only about 3% increase in the income of vegetable farmers participating in irrigated vegetable production using SRs against the counterfactual situation but this change is insignificant statistically. The current low level effectiveness and impact of SRs could be enhanced by improving their management, for example, through the provision of incentive mechanisms such as subsidies to the private sector involvement in rehabilitation, management and irrigation service provision and strengthening the capacity of existing water users associations. Furthermore, small reserviors should be recognized not only as water sources for small scale irrigation but also as providers of multiple livelihood benefits to local communities and consequently should attract due attention in public resource allocation in their rehabilitation and management/institutional capacity building.